Short-term effects of self-massage combined with home exercise on pain, daily activity, and autonomic function in patients with myofascial pain dysfunction syndrome - Chen, Liang-Cheng; Wang, Tzyy-Jiuan; Chang, Shin-Tsu; Lin, Shiou-Ping; Chang, Cheng-Chiang; Chan, Yuan-Chi; Chu, Heng-Yi (Journal of Physical Therapy Science, 2015)
[Purpose] The aim of the present was to investigate the short-term effects of a program combining self-massage and home exercise for patients with myofascial pain dysfunction syndrome (MPDS). [Subjects and Methods] In this retrospective study, 63 patients were allocated to the experimental (n = 32) and control (n = 31) groups. Both groups received 6 sessions of treatment with physical modalities over the course of two weeks. The experimental group completed an additional program with a combination of self-massage and home exercise. The outcome measurements included a pain scale, pressure pain threshold (PPT), neck disability index (NDI), patient-specific functional scales (PSFS), and heart rate variability (HRV). The interactions between the groups and over time were analyzed using two-way repeated measures ANOVA. [Results] Only the experimental group demonstrated significant improvements in the pain scale with varying conditions. The PPTs of the trigger points increased significantly in the experimental group, and significant functional improvements in NDI and PSFS were observed in the same group. There were significant increases in high-frequency HRV and high-frequency % in the experimental group. [Conclusion] Treatment with physical modalities plus combination of self-massage and home exercise is more effective than the physical modalities treatment alone.